Pendekatan AISAS Dalam Post Instagram Carousel Sebagai Strategi Promosi Pada Museum Ranggawarsita - Ristia Kadiasti; Mukaromah Mukaromah (ULTIMART Jurnal Komunikasi Visual, 2022)
Social Media as a medium of information that is able to become a communication bridge between humans is used by various communities to disseminate information with various purposes, especially in terms of marketing. One of the theories used in marketing science such as AISAS (Attention, Interest, Search, Action, Share) is used as the basis for various communities to gain public attention on social media. One of the stakeholders in this community is the Ranggawarsita Museum, Central Java, which actively disseminates information through social media platforms, namely Instagram. However, the Ranggawarsita Museum as a research partner has an urgent need for the dissemination of information involving complex data about museum collections into the Instagram platform. This complex data can be expressed in the form of infographics through the Instagram platform in the form of a carousel. The Carousel form on the Instagram platform is able to increase interest and complex information in one link. Keywords: AISAS; infographic; instagram carousel; museum.